The importance of applicants’ personal qualities in selection and training psychologists - Lipiets, Zoriana (Lviv Polytechnic Publishing House, 2015)
The article contains some requirements for the psychologist as an individual and characteristics of the selection process for students to study psychology. There are many requirements for a person to become a psychologist, which include physical condition, mental health, intelligence, etc., but there is no a University that makes any researches to ensure those criteria in students that is educating. Obviously, nothing can be investigated or evaluated completely, but it would be more responsible and ecological to select applicants carefully for specialties that are socially significant. Ukraine does not have any systems of evaluating the candidates for education that take into consideration their individual features; this topic requires deep analysis and further study.
Keywords: applicant; psychologist; personality; empathy; competence; counselors; characteristics